Answer:
[tex]p=6+2 \sqrt{5}, p=6-2 \sqrt{5}[/tex]
Step-by-step explanation:
Step 1: Given expression is [tex](p-4)^{2}=4 p[/tex].
Step 2: To write the equation in the quadratic form, subtract 4p from both sides of the equation.
[tex]\Rightarrow(p-4)^{2}-4 p=4 p-4 p[/tex]
[tex]\Rightarrow p^{2}-8 p+16-4 p=0[/tex]
[tex]\Rightarrow p^{2}-12 p+16=0[/tex]
[tex]\Rightarrow p^{2}-12 p=-16[/tex]
Step 3 :Add[tex]\left(\frac{-12}{2}\right)^{2}[/tex] on both sides of the equation.
[tex]\Rightarrow p^{2}-12 p+\left(\frac{-12}{2}\right)^{2}=-16+\left(\frac{-12}{2}\right)^{2}[/tex]
[tex]\Rightarrow p^{2}-12 p+36=-16+36[/tex]
[tex]\Rightarrow(p-6)^{2}=20[/tex]
Step 4: Taking square root on both sides of the equation.
[tex](p-6)=\pm \sqrt{20}[/tex]
[tex]p=6 \pm 2 \sqrt{5}[/tex]
Hence, [tex]p=6+2 \sqrt{5}, p=6-2 \sqrt{5}[/tex].